UMKM Berdaya: Kreativitas Berbasis Internet dan Pemasaran Digital di Desa Tenggayun - Nurmahadi Nurmahadi; Dito Wahyutomo; Lukman Hakim; Irawan Fakhrudin Mahali Zikri (jurnal ABDIMAS Indonesia, 2024)
Tenggayun Village has great potential for the development of MSMEs (Micro, Small, and Medium Enterprises), but many business owners have not yet utilized digital technology for marketing. This program aims to enhance the creativity of MSME actors through education and training in digital marketing. The training covers how to use digital platforms, manage social media accounts, and e-commerce. After completing the program, participants showed improved knowledge and skills in creating engaging content and leveraging online marketing to increase sales. As a result, many MSME owners were able to reach new customers and boost their revenue. The program also encourages creativity in product development, leading to more innovative products. Additionally, a community was formed among MSME actors who supported one another. The program increased public awareness of the importance of purchasing local products, strengthening the market for MSME products. Moving forward, the service team plans to conduct regular monitoring to ensure the sustainability of digital marketing practices. Overall, this program has had a positive impact on the local economy, strengthening the competitiveness of MSMEs in Tenggayun Village.